Simulation of Corrosion Induced Damage of Reinforced Concrete - Ahmed, Shaikh; Larner, Matthew (Engineers Australia, 2012)
This paper presents a finite element (FE) based numerical model to simulate the corrosion-induced cracking of reinforced concrete. Both uniform and non-uniform corrosion of steel in concrete is simulated. The effect of non-uniform corrosion distribution, cover depths, cover-to-rebar diameter ratio and compressive strengths of concrete on the cracking and cracking pressure are studied. The results indicate that the pressure required to cause the cracking of concrete cover under non-uniform corrosion are much smaller, between 40% and 50%, than those under uniform corrosion. The model predicts that the pressure require to cause the cracking of the concrete cover increases as the concrete compressive strength increases. It is also found that as the cover to rebar diameter ratio is increased, the pressure require to cause the cracking of concrete cover increases with a linear relationship between cover depth-to-rebar diameter ratio and pressure required to cause cracking of the concrete cover. The model is also verified with the experimental results.